2013
DOI: 10.1002/jhm.2009
|View full text |Cite
|
Sign up to set email alerts
|

A trial of a real‐time Alert for clinical deterioration in Patients hospitalized on general medical wards

Abstract: BACKGROUND With limited numbers of intensive care unit (ICU) beds available, increasing patient acuity is expected to contribute to episodes of inpatient deterioration on general wards. OBJECTIVE To prospectively validate a predictive algorithm for clinical deterioration in general–medical ward patients, and to conduct a trial of real‐time alerts based on this algorithm. DESIGN Randomized, controlled crossover study. SETTING/PATIENTS Academic center with patients hospitalized on 8 general wards between July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
135
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(141 citation statements)
references
References 36 publications
1
135
1
4
Order By: Relevance
“…Our simple treatment of vital sign abnormalities as markers of SIRS is not as elaborate as in many EWSs. Our study is only hypothesis-generating, whereas several EWSs are well validated (25,32). We cannot provide data on how our alert might change bedside interventions by clinicians.…”
Section: * Our Data Indicate That Rrt Activation Would Occur About Twmentioning
confidence: 91%
See 2 more Smart Citations
“…Our simple treatment of vital sign abnormalities as markers of SIRS is not as elaborate as in many EWSs. Our study is only hypothesis-generating, whereas several EWSs are well validated (25,32). We cannot provide data on how our alert might change bedside interventions by clinicians.…”
Section: * Our Data Indicate That Rrt Activation Would Occur About Twmentioning
confidence: 91%
“…One review of 39 EWSs reported PPVs ranging from 13.5-26.1% (34), and another review of 25 systems reported a median PPV of 36.7% with interquartile range 29.3-43.8% (34). PPV was not reported for several of the most elegant and well-studied EWSs (22,23,25,32). From the perspective of bedside clinicians and rapid response team members, the efficiency of an alert system is strongly influenced by the PPV, because a poor PPV translates to frequent false alerts.…”
Section: * Our Data Indicate That Rrt Activation Would Occur About Twmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of communication and action may explain the conflicting findings reported by Smith and others. 7 To improve communication, Bailey and colleagues 8 added an EWS alert to the medical-surgical charge nurse's pager but could not explain a lack of improvement in patients' outcomes, suggesting that a more integrated approach to identify interventions is needed. Jackson and others 9 reported a strong negative correlation between medical-surgical nurses' years of experience and reluctance to activate an RRT call.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to improve identification of objective criteria indicating clinical deterioration, objective data, real-time alerts to nursing staff, and automated monitors have been implemented with conflicting impact on outcome measures. 15,[20][21][22][23] The activation of the RRT is likely based not only on objective information but also on the nurse forming a clinical judgment about the situation and seeking assistance within the context of their organizational cultures.…”
mentioning
confidence: 99%